Elastic shear buckling coefficients for diagonally stiffened webs. (February 2022) - Martins, J.P.; Cardoso, H.S.
Abstract: In this paper, the characterisation of the elastic shear buckling behaviour of simply supported plates diagonally stiffened excluding the influence of direct stresses is made. Two broad numerical parametric studies consisting of linear buckling analysis by the finite element method are performed, covering the entire practical range of critical parameters like the aspect ratio and the stiffener's mechanical properties. In the first parametric study, attention is given to the influence of each parameter in the elastic critical shear stress. For that reason, a beam FE is chosen to model the stiffener, allowing the variation of each parameter individually. As it is systematically disregarded in previous studies, particular attention is given to the effect of the stiffener's torsional rigidity. The numerical models used in the second parametric study consist of full-shell FE, and the results are used to perform regression analysis that ultimately allowed to proposed two mathematical models for the analytical calculation of the elastic shear buckling coefficient: for open stiffeners over the compression diagonal and for closed cross-section stiffeners over the compression diagonal. The proposed mathematical models present excellent accuracy. Highlights: The elastic shear buckling behaviour of simply supported diagonally stiffened plates is thoroughly characterised. Models to analytically determine the elastic shear buckling coefficients are proposed. The effect of the stiffner torsional rigidity if analysed and included in the proposed mathematical models.